KLASIFIKASI DAN FUNGSI PERIBAHASA DALAM MASYARAKAT BANJAR The Classification and Functional of Banjarese’s Proverb. - SITI JAMZAROH; Eka Suryatin (Balai Bahasa Sulawesi Tengah, 2021)
This study aims to a) describe the classification of Banjar proverbs based on S. Keyzer; and b) describe the function of proverbs in Banjar society. This research is descriptive qualitative. Data collection using SBLC technique and recording technique. The data are in the form of Banjarese proverbs or expressions contained in the book Paribasa Urang by Syamsiar Semar. The data is processed by being classified based on the S. Keyzer grouping. The results showed that based on S. Keyzer's classification, Banjar proverbs were classified as: a) animal proverbs; b) group of plant proverbs; c) group of human proverbs; d) group of kinship proverbs; e) group of body function proverbs; 2) The functions of Banjar proverbs include 1) a mirror or projection of the owner's imagination, 2) a tool for ratifying the institutions of cultural institutions, 3) an educational tool, and 4) a means of suppressing or forcing the implementation of community values (means of social pressure), and controlling behavior. community (exercion social control).Key words: proverbs, education, values